Improving Power-Conversion Efficiency via a Hybrid MPPT Approach for Photovoltaic Systems - Ma, J.; Man, K. L.; Zhang, N.; Guan, S. U.; Wong, P. W.H.; Lim, E. G.; Krilavicius, T.; Kapociute-Dzikiene, J.; Lei, C. U. (Elektronika ir Elektrotechnika, 2013)
This paper presents a hybrid Maximum Power Point Tracking (MPPT) method for improving the power –conversion efficiency of Photovoltaic (PV) generators. By detecting the output power changes caused by environmental reasons, the proposed method performs variable-step online search process with an accurate estimation of the Maximum Power Point (MPP) locus. A PV generator with a Single Ended Primary Inductance Converter (SEPIC) is developed in PSIM to verify the feasibility and suitability of the proposed method. Simulation results show that it can not only deliver a stable reference operating voltage for MPPs at steady state, but also can speed up the searching process under rapidly changing environment conditions. DOI: http://dx.doi.org/10.5755/j01.eee.19.7.5163